(untitled) (Global Journal of Human-Social Science, 2024)
Based on a bibliographical review and re-readings of different authors we aim to bring visibility to the discussion regarding intermodal bilingualism and consequently to present a reflection on the acquisition of the first and second languages L1 and L2 by deaf children We aim to highlight the importance of the first language in this case sign language as a means for developing competence in the second language the oral language in its written modality We divided the article into an explanation of the contact of deaf children with sign language SL as their first language It discusses the development of oral language OL as the second language first addressing writing and then moving on to issues related to reading Finally it reflects on using visual resources and how these visual modes can enhance the second language teaching and learning process for deaf children